Learning-by-doing, government spending and economic growth: a model à la Matsuyama-Barro - Ortiz, Carlos Humberto (CIDSE, Centro de Investigaciones y Documentación Socioeconomica, 2021)
Learning-by-doing and external productive effects of government spending are well-known engines of long-run economic growth. To the best of our knowledge, the interaction of these growth engines has not been analysed. This paper aims at filling this vacuum by combining the approaches of Matsuyama (1992) and Barro (1990). In the ensuing model, industrialization and growth are directly related. Governments may play a role in industrialization by adopting an optimal fiscal policy, and through improving efficiency. There is also room for industrial policies that lead to an optimal allocation of resources. The latter possibility is in contradiction to an open commercial regime that leads to deindustrialization. The model is used to think about some development experiences, specially about the slowdown of the Colombian economy since the 1980s.